Visible light accelerates the ultraviolet A‐induced degradation of eumelanin and pheomelanin. (11th December 2018) - Ito, Shosuke; Kolbe, Ludger; Weets, Gudrun; Wakamatsu, Kazumasa
Abstract: Exposure to excess ultraviolet (UV) A radiation induces the degradation/modification of both eumelanin and pheomelanin that may be deleterious to pigmented tissues. Although the spectral distribution of solar energy comprises nearly half of visible light (VL), few studies have been conducted to examine the role of VL in the photodegradation of both types of melanin, either VL alone or in combination with UVA. In this study, we examined the effects of physiological doses of VL (150 to 300 J cm −2 ) alone or in combination with a physiological dose of UVA (20 J cm −2 ) in normal human epidermal melanocytes. The degradation/modification of melanin structures was evaluated by our chemical degradation—high performance liquid chromatography methods. The results show that VL accelerates UVA‐induced changes in the structural features of both eumelanin and pheomelanin, although VL or UVA alone induced only minor changes in melanin structure. The differential spectral method provides support for the additive effects of VL.